2011
DOI: 10.2138/am.2011.3464
|View full text |Cite
|
Sign up to set email alerts
|

XAS determination of the Fe local environment and oxidation state in phonolite glasses

Abstract: The Fe oxidation state, coordination geometry, and (Fe-O) distances have been determined by Fe K-edge XANES and EXAFS for a set of silicate glasses of phonolite composition produced at different oxygen fugacity conditions with the aim of determining the effect of iron oxidation state and local structural environment on the viscosity of the corresponding melts. Comparison of the pre-edge peak data with those of Fe model compounds with known oxidation state and coordination number allowed for determination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 21 publications
6
33
0
1
Order By: Relevance
“…Chemical analyses are reported in Table 1. Iron oxidation state (Fe 2+ /Fe 3+ ratio) was determined by redox titration using dichromate (K 2 Cr 2 O 7 ) for FeO at LMU-Munich (Giuli et al, 2011) for both anhydrous (Table 1) and selected hydrous glasses (Table 2). Water-bearing samples, containing up to 3.55 wt.%, were synthesized using a rapid-quench internally-heated pressure vessel (IHPV, Hannover University).…”
Section: Experimental Rationalementioning
confidence: 99%
“…Chemical analyses are reported in Table 1. Iron oxidation state (Fe 2+ /Fe 3+ ratio) was determined by redox titration using dichromate (K 2 Cr 2 O 7 ) for FeO at LMU-Munich (Giuli et al, 2011) for both anhydrous (Table 1) and selected hydrous glasses (Table 2). Water-bearing samples, containing up to 3.55 wt.%, were synthesized using a rapid-quench internally-heated pressure vessel (IHPV, Hannover University).…”
Section: Experimental Rationalementioning
confidence: 99%
“…[26]. As other trivalent cations, Fe 3+ is generally accommodated in natural glasses as a network former [27,28]. The changes in the oxidation states of iron upon ionizing radiations have been the subject of many studies, e.g.…”
Section: Fe 3+ In Trace and Minor Amounts In Glassesmentioning
confidence: 99%
“…Le Losq and Neuville (2013) have recently studied the effect of Na/K ratio on the structure and rheology of silica-rich glasses, proposing the occurrence of two sub-networks in mixed alkali tectosilicate glasses. In previous experiments on phonolite glasses (with constant alkali content), we determined that the oxidation of Fe produces an increase in polymerization as well as shorter (and stronger) Fe-O bonds (Giuli et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…The common Fe species interpreted from investigations of silicate melts and glasses include [4] Fe 2+ , [5] Fe 2+ , [4] Fe 3+ , and [5] Fe 3+ (see Wilke et al 2001;Giuli et al 2002Giuli et al , 2011Giuli et al , 2012aJackson et al 2005;Métrich et al 2006;Rossano et al 2008). The presence of [6] Fe 2+ (e.g., Calas and Petiau 1983;Virgo and Mysen 1985;Dingwell and Virgo 1987) and a minor presence of [6] Fe 3+ (Wilke et al 2007) have been reported.…”
Section: Introductionmentioning
confidence: 99%